Analisis Yuridis Peranan Notaris Dalam Pemenuhan Prinsip Syariah Dalam Akta Pada Akad Pembiayaan Murabahah Di Perbankan Syariah - Zarwan Sudirman; Zainuddin Zainuddin; Sahban Sahban (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: This study aims to determine and analyze the implementation of sharia principles in the murabahah financing agreement deed in Islamic banking. Tofind out and analyze the role of a notary in the implementation of sharia principles in the murabahah financing agreement deed in Islamic banking. This type of research is normative juridical with a statutory approach. The results of this study indicate that the principles implemented by the notary in making the deed are: the principle of voluntary, the principle of keeping promises, the principle of prudence, the principle of certainty, the principle of mutual benefit, the principle of equality, the principle of honesty andtransparency, the principle of ability, the principle of convenience. The role of a notary in making an authentic deed in every business agreement in Islamic banking is very important. The notary is not only directly related to his authority in making the authentic deed required in the cooperation, but also other agreements made between Islamic banks and customers to get more guarantees of legal certainty for both parties. The suggestion from this research is that a notary or PPAT official in making a deed for the benefit of a Sharia contract, should continue to prioritize Sharia principles. The government should in making regulations related to the position of a notary for the benefit of sharia economic transactions should include sharia principles or principles that must be carried out by a notary or PPAT official. Abstrak: Penelitian ini berujuan untuk mengetahui dan menganalisis pelaksanaan prinsip-prinsip syariah dalam akta akad pembiayaan murabahah padaperbankan Syariah. Untuk mengetahui dan menganalisis peranan notaris dalam pelaksanaan prinsip-prinsip syariah dalam akta akad pembiayaan murabahah pada perbankan Syariah. Tipe penelitian ini adalah yuridis normatif dengan pendekatan perundang-undangan. Hasil penelitian ini menunjukkan bahwa prinsip prinsip yang diimplementasikan notaris dalam pembuatan akta yaitu: prinsip sukarela, asas menepati janji, prinsip kehati-hatian, prinsip kepastian, prinsip saling menguntungkan, prinsip kesetaraan, prinsip kejujuran dan transparansi, prinsip kemampuan, prinsip kemudahan.Peranan notaris dalam pembuatan akta otentik dalam setiap perjanjian bisnis di perbankan syariah sangatlah penting. Notaris bukan hanya berkaitan langsung dengan kewenangannya di dalam pembuatan akta otentik yang diperlukan dalam kerja sama tersebut, namun juga perjanjian-perjanjian lainnya yang dibuat antara bank syariah dengan nasabah untuk lebih mendapatkan jaminan kepastian hukum bagi kedua belah pihak. Sarandari penelitian ini adalah, notaris atau Pejabat PPAT dalam membuat akta untuk kepentingan akad Syariah, hendaknya tetap mengedepankan prinsip- prinsip Syariah. Hendaknya pemerintah dalam membuat peraturan-peraturan terkait jabatan notaris untuk kepentingan transaksi ekonomi Syariah hendaknya mencantumkan asas-asas atau prinsip-prinsip syariah yang harus dilakansakan oleh Notaris atau Pejabat PPAT.